The Transformasi Proses Bisnis Produk Asuransi Rangka Kapal di Reasuransi PT. ABC - Renny Rahmadi Putra; Nurmala Nurmala (Journal of Management and Bussines (JOMB), 2024)
This research aims to (1) analyze the ongoing H&M insurance business process, (2) identify the root of the problems that hinder the effectiveness of the business process, (3) evaluate underwriting parameters, and (4) design a new business model in PT reinsurance. A B C. The research method used is qualitative analysis involving the Delphi method of seven H&M insurance industry experts who were chosen deliberately. The business model is explained through the Business Process Model and Notation (BPMN). Business process analysis is carried out using root-cause analysis, value-added analysis, waste analysis, and direct weighting analysis to determine the relevance of underwriting parameters. Business transformation is carried out by (1) adding significant risk parameters in the underwriting process, (2) eliminating activities that do not provide added value, (3) increasing risk analysis activities that provide added value to the business acceptance process (underwriting), (4) improving data management through optimizing administration as a data bank and system agent, and (5) implementing pricing rates to maintain stability of rates and premiums. Statistical analysis supports risk assessment and pricing rates to ensure adequate premiums required for further research. In conclusion, a holistic business process transformation accompanied by improved risk analysis and data management is needed to increase the profitability and sustainability of the ship hull insurance industry. Keywords: Ship Hull Insurance, Business Process Management, Business Process Model and Notation (BPMN), Business Process Transformation